SMALL CLASTS AND ORE GENERATION - Vladimirov P.S.; Dolgopolov V.M.; Dolivo-Dobrovolskaya G.I. (My University, 1990)
Small clasts (SC's), generated by mechanical and other comminutive action on minerals, have many anomalous properties which justify treating them as a special aggregational state. Their anomalous character and variable properties result from the mobile lattice defects that are abundant within these small crystals. Extensive investigations related to the development of new ore processing technologies have recently led to the systematization of a variety of experimental data on the processing of minerals and on various related subjects. These investigations revealed patterns of behavior of small clasts, which prove to have extremely high chemical reactivities. Thus, the clastic material of the natural phases of SC's is a concentrator and in many cases a sorbent for rare or minor elements. For example, an important factor influencing the concentration of uranium is the presence of finely-divided mineral phases, e.g., the clay fraction in sandstone, carbonaceous matter in shale, and fine-grained sulfide minerals. The uranium mineralization is also controlled to a significant degree by tectonic faults and karst structures. It therefore appears that the importance of the SC phases in natural mineralization processes (and particularly in ore deposition) is larger than in industrial processes.